AKUNTANSI PENILAIAN DAN PENCATATAN PERSEDIAAN STONEWAREMENJADI BAHAN BAKU KERAMIK SEBAGAI DASAR PENENTUAN LABA KOTOR YANG WAJAR MENURUT TEORI AKUNTANSI KEUANGAN - I Nyoman Normal; I Wayan Wardita (Forum Manajemen, 2014)
The aims of this research that relate stoneware inventory to ceramics rawmaterial were : (1) Calculate value of ending inventory as component of current assetby inventory valuation method; (2) Calculate of cost of goods soldas component ofincome statement; (3) Record of ending inventory and cost of goods sold use phisicand perpectual method; and (4) Determinate influence ofinventory valuation methodto grossprofit. The research results that relate stoneware to ceramics raw materialwere : (1)The using of recording method (physic and perpectual) and valuation (firstin first out, last in first out, and moving average) at UPT PSTKP Bali technologyservices influence of financial statements element, such as ending inventory, cost ofgoods sold, and gross profit; (2) The using of physic method into record stonewarecould influence : (a) ending inventory : decrease 4,37% (last in first out method),decrease 1,17% (weighted average method), (b) cost of goods sold : increase 0,09%(last in first out method), increase 0,02% (weighted average method), (c)grossprofit : decrease 1,02% (last in first out method), decrease 0,27% (weighted averagemethod); (3) The using of perpectual method into record stoneware could influence :(a) ending inventory : decrease 1,26% (first in first out method), decrease 4,37% (lastin first out method), increase 2,76% (moving average method), (b) cost of goods sold: decrease 0,08% (first in first out method), increase 0,09% (last in first out method),decrease 0,05% (moving average method), (c)gross profit : increase 0,91% (firstin first out method), decrease 1,02% (last in first out method), and increase 0,65%(moving average method); (4) If the buying price is increase too, so that the using offirst in first out method would increase ending inventory, decrease cost of goods sold,and increase gross profit; and (5) If the buying price is decrease too, so that the usingof first in first out method would decrease ending inventory, increase cost of goodssold, and decrease gross profit.